Social public policies and territory: Dimensions and impacts in the fight against social vulnerabilities - Faria , Everton Henry (Seven Editora, 2023)
Since the construction and promulgation of our last Constitution in 1988, much has been discussed in Brazil about the implementation of social public policies at the regional and local levels, especially about the unprecedented forms of organization of the territory to meet the demands of society. In recent years, several researches and studies have been occupied with multiple themes attempting the construction of a conceptual theoretical framework (a social theory) capable of questioning, apprehending and understanding this new process of organization of the provision of public services. In this context, the Social Assistance policy established in the Brazilian scenario a set of actions in order to reduce the social inequalities existing in the most diverse territories of Brazilian cities. Nevertheless, in the last decade the territory has become one of the most important dimensions in the establishment of the organization of social public policies in Brazil, especially when it comes to the public policy of Social Assistance. Considering this new scenario of national policy based on a rich bibliography produced on this subject, especially about the forms, roles and challenges of the territory, we note that there are still many issues to be studied and understood, especially when it comes to the implementation of a public policy that has in its organizational axes the territory as one of the central elements of its functioning. Thus, the objective of this work is to understand the dimensions of territorial organization for the effectiveness of social public policies from the implementation of the Unified Social Assistance System (SUAS) in 2005, focusing on the actions developed by the Ministry of Social Development and Fight against Hunger – MDS in the organization of the territory to meet and combat social vulnerabilities in the perspective of political-administrative decentralization. The applied methodology consists of qualitative and quantitative research methods, defining itself as a mixed methodology. DOI:https://doi.org/10.56238/devopinterscie-157